Vaginal cuff dehiscence after laparoscopic trachelectomy post hysterectomy: a case report and brief review of the literature - Kalogeropoulos, Sotirios; Chronopoulou, Elpiniki; Iliopoulos, Evangelos; Decavalas, Georgios (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Vaginal cuff dehiscence (VCD) is a serious complication of total laparoscopic hysterectomy (TLH) or trachelectomy with high morbidity, as it can potentially lead to evisceration/bowel ischemia and sepsis. Authors present a case report of vaginal cuff dehiscence after laparoscopic trachelectomy. The patient reported post-coital onset of symptoms. She presented with acute abdomen and required urgent surgical intervention. In this case surgical management was dictated by the clinical manifestation. However, authors argue that conservative management is also an option for some of these patients and the decision regarding the management plan should be personalized according to the clinical presentation and the patient’s expectations. Emphasis should be given to avoid early onset of sexual activity during the immediate recovery period. Compared to women who underwent an abdominal or vaginal hysterectomy, those who had a laparoscopic procedure have less post-operative pain, shorter recovery period and often they are advised to return early to their normal habits and their work place. It is expected that this group of patients feel well enough to resume sexual activity soon after their procedure. Therefore, our counselling is of paramount importance as it should be highlighted that sexual intercourse is possibly the most common triggering event for VCD which a serious complication with severe morbidity is. The resumption should, therefore, follow medical consultation and be individualized according to co-morbidities which could affect healing, intraoperative findings and evaluation of the whole recovery progress.